Bimbingan Islam dalam Menumbuhkan Kepercayaan Diri Penyintas HIV/AIDS - Nur Ikha Wijayanto; Sholihan, Sholihan; Mintarsih, Widayat (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2023)
Purpose: The purpose of this study is how the implementation of Islamic guidance in fostering self-confidence of HIV / AIDS survivors at PKBI Semarang City. Method: This type of research is field research with a phenomenological approach. Data was obtained using observation method, interview method, documentation method. The data that has been collected is analyzed by the stages of data reduction, data display and data verification / conclusion drawing. Result: The results showed that the implementation of Islamic guidance in fostering self-confidence of HIV/AIDS survivors in PKBI Semarang City focuses in three steps, namely planning, implementation and evaluation. Planning is done by the supervisor by making preparations to help make it easier to carry out Islamic guidance. Implementation is done by providing Islamic guidance material related to monotheism, sharia or moral worship with spiritual material programs, psychological, social guidance, which emphasizes individual and group approaches through lecture, question and answer, discussion, experiment demonstration, habituation, out bond and motivational training based on efforts to increase self-resilience and self-confidence of HIV / AIDS survivors by promoting motivation to always get closer to Allah through repentance, patience, effort and tawakkal so that HIV / AIDS survivors feel close to Allah SWT and able to live their lives with confidence. Evaluation is always carried out to control how far the absorption ability of HIV / AIDS survivors and assess the behavior of HIV/ AIDS survivors after implementing Islamic guidance